DEVELOPMENT OF CLOPEDIMATIC LEARNING MEDIA WITH REALISTIC MATHEMATICS APPROACH BASED ON MADURA’S LOCAL WISDOM - Septi Dariyatul Aini; Agus Subaidi; Chairul Fajar Tafrilyanto (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The low student learning outcomes in the measurement material can be caused by the tendency of teachers to only transfer their knowledge to students' minds so that students are passive, and not critical. One learning approach that pays attention to this situation is a realistic mathematical approach based on Madura local wisdom. Students are presented with contextual problems, namely problems related to measurements, so that they are trained to get used to solving problems in their daily lives. To support this realistic mathematics approach, a clopedimatics-based learning media will be designed as a substitute for textbooks used by students. Clopedimatics is a form of print media that is compiled based on the concept of compiling an Encyclopedia and designed to help students master the measurement material and is associated with non-standard units of measurement used by the Madurese community. This type of research is development research that uses a 4-D model but has been modified to 3-D, namely defining, designing, and developing. The conclusions of this study are development of clopedimatic learning media with a realistic mathematics approach based on Madurese local wisdom in the measurement material at SDN Barkot 1 Pamekasan meets the valid, practical, and effective criteria.